Recent weathering promotes C storage inside large phyllosilicate particles in forest soil. (1st February 2022) - Van Der Kellen, Ingride; Derrien, Delphine; Ghanbaja, Jaafar; Turpault, Marie-Pierre
Abstract: Mineral weathering in soils is expected to promote chemical and physical interactions between soil organic matter and mineral phases, which are known to enhance the protection of organic matter from decomposition. The investigation of mineral-organic associations (MOAs) formation during weathering is therefore crucial to understanding carbon storage processes in soils. Until now studies have been mainly conducted by building inferences from soil characteristics, through short-term laboratory experiments in simplified conditions, or over very long-term time scales using soil chronosequences. Weathering can significantly alter the mineral matrix at the annual timescale, but knowledge regarding MOA formation processes occurring in situ, over short time scales and during the first stage of mineral weathering is lacking. To fill this gap, we performed a mesh bag incubation containing large Na-saturated and organic carbon-free vermiculite particles (200–400 µm in size) in acidic soil of a Douglas-fir forest, in the Beaujolais area (France). The vermiculite bags were deposited at the interface between the forest floor and the mineral soil, where intense weathering occurs. After 20 years of soil incubation, the weathered vermiculite particles were collected and characterized at the macroscale (X ray diffraction and physicochemical analyses), at the microscale (scanning electron microscopy-SEM imaging and element mapping) and at the nanoscale (transmission electron microscopy-TEM imaging, element mapping and speciation by electron energy loss spectroscopy-EELS) on a focus ion beam (FIB) section exposing the inside section of vermiculite particles. Cation exchange capacity, exchangeable cations and elemental analysis of the vermiculite particles showed important changes after 20 years of incubation. The initial exchangeable Na pool was completely depleted. The cation exchange capacity strongly decreased from 178.1 cmolc kg −1 to 49.2 cmolc kg −1 due to interlayer hydroxylation of the weathered vermiculite. The weathering budget indicated a 10% vermiculite dissolution and an organic carbon (C) enrichment of 5 mg g −1 . Microscope images and elemental mapping of control vermiculite particles (nonincubated) showed a flat, smooth surface morphology with no detected C. In contrast, 20-year weathered vermiculite particles showed irregular outer- and inner-surfaces marked by multiple cracks from chemical dissolution. Some nano- and microscale exfoliation spaces filled with C were observed inside the weathered particles. C in association with Ca occurred in nanoscale exfoliation spaces. C also occurred entrapped in nanocrystalline Mn oxides (hausmannite) or K-rich aluminosilicates, which precipitated in micro-sized exfoliation spaces. These observations indicated that C storage inside the altered vermiculite particles was both mediated by chemical binding and physical entrapment. The functional groups of the organic matter revealed by EELS spectroscopy strongly differed between nano- and microscale exfoliation spaces. This study using the mineral bag incubation method provides evidence of new processes driving C storage inside large phyllosilicate particles during their initial and recent weathering, which could contribute to long-term C stabilization.